EMBRACING SUSTAINABLE MARKETING IN HIGHER EDUCATION VIEWED THROUGH SERVICE QUALITY: STUDENTS' PERSPECTIVE (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2024)
Purpose: This paper explores the application of sustainable marketing practices in higher education insti-tutions, focusing in particular on the perspectives and experiences of students as direct users of the service. Given that sustainability has become an important issue globally, integration of sustainable principles into the marketing strategies of educational institutions becomes imperative. It was found that the existing academic literature contains only a very limited number of studies in the area of applying sustainable mar-keting in public higher education institutions, despite its recognized importance. This study aims to help close this gap.Methodology: Using a quantitative research methodology, including questionnaires, this study examines student perceptions and attitudes towards the application of sustainable marketing in higher education, focusing on the quality of services. A structural model was tested, the reliability and validity of which had been confirmed previously. Partial least squares structural equation modeling (PLS-SEM) was used to ex-amine the relationships between the constructs.Results: All direct relationships in the structural model were found to be statistically significant and posi-tive, confirming the hypothesis that sustainable marketing of a higher education institution has a positive impact on the performance of the higher education institution when considering the quality of services.Conclusion: By highlighting the importance of sustainable marketing in public higher education institu-tions, this research contributes to the growing sustainability discourse in the academic community and provides actionable insights for educational institutions seeking to improve their marketing strategies in line with environmental and social responsibility goals.